Buying behavior of target family households of ready-to-drink milk - Divinagracia, Ma Rochelle G. (Animo Repository, 2002)
This study probes into the differences in and influence of buying behavior that mothers-wives manifest in their capacity as members of a household on milk purchases. A survey, which involved 75 middle-class family households who reside in subdivisions that are close to the biggest supermarket chain as the source of information, was conducted. Two survey instruments were used to determine the consumer markets of RTD milk was well as the degree of buyer involvement in the purchase decision of RTD milk. Descriptive statistics such as the mean and standard deviation were computed. Factor analysis was employed to identify two sets of best linear combination of variables consisting of measures of buyer involvement and dimensions of buying behavior. The relationship between the dimensions of buying behavior and buyer's decision were further analyzed using the ordinary least squares regression method. Moreover, the t-test was employed to validate differences in the buying behavior, buyer's decision, and in the degree of buyer involvement. The major findings and conclusions of the study are (1) moderate to high buyer involvement on purchase decisions, (2) moderate perceived differences among brands, (3) presence of cognitive influences in purchase decisions and brand choice, and (4) high buyer involvement for both working and non-working wives. Marketers must prepare an expected product through the inclusion of attributes that buyers look for when they purchase RTD milk. In this study, the top attributes that buyers ranked important in the purchase of RTD milk are (1) gives vitamins and essential nutrients (2) great taste and (3) substitutes solid food. This can be accomplished through product differentiation and product pricing. As the demand for RTD milk rapidly grows, marketers are expected to improve product quality and enhance product features through product reformulation. Marketers need to be tasked in clearly communicating the reformulated product's nutritional advantage (over substitute beverages and imported RTD milk brands) to the target households. The author has developed a marketing template for local processors of RTD milk.